Jurong BirdPark : making a business out of the birds. - Goh, Wee Tiong. (2008)
The purpose of this study is to examine the present and future outlook for one of Singapore’s top tourist attractions, Jurong BirdPark. In particular, the external and internal environments of the tourist attraction are examined. Throughout our investigations using conceptual frameworks and statistical analysis, the strengths, weaknesses, opportunities and threats of Jurong BirdPark are all noted and analyzed to provide us with an overall view of what Jurong BirdPark, as a company, is facing.